Single‐stage ACL reconstruction and displaced bucket handle Meniscus repair is associated with lower Meniscus repair failure rates compared to two‐stage surgery - Carolina Kekki; Riccardo Cristiani; Anders Stålman; Christoffer vonEssen (Journal of Experimental Orthopaedics)
Abstract Purpose To compare displaced bucket‐handle meniscus repair (BHMR) failure rates, subjective and objective knee function after BHMR in the setting of ACLR performed as a single‐or two‐stage procedure, and assess factors associated with BHMR survival. Methods This retrospective study included patients who underwent surgery between February 2015 and December 2021 at one institution. Patients with a displaced bucket‐handle meniscus tear (BHMT) and ACL‐injury undergoing BHMR and ACLR as a single‐ (concomitant BHMR and ACLR) or two‐stage (BHMR and subsequent ACLR) procedure were identified. The primary outcome was the 2‐year BHMR failure rate following ACLR, defined as reoperation with meniscus re‐repair or resection. Additionally, 6‐month range of motion (ROM), isokinetic knee (extension, flexion) strength, 1‐and 2‐year Knee injury and Osteoarthritis Outcome Score (KOOS), Patient‐acceptable symptom state (PASS), treatment failure (TF) were compared between the groups. Kaplan‐Meier analysis was performed to assess BHMR survival, factors associated with repair survival were analysed through Cox proportional hazard regression analysis. Results The cohort included 159 displaced BHMRs, 120 (75.5%) underwent single‐stage surgery. The overall BHMR failure rate was 27% (43/159). The single‐stage surgery group had significantly lower failure rate (15% vs. 35.9%, p = 0.006). BHMT laterality, subjective (KOOS, PASS and TF) and objective (ROM, isokinetic strength) knee function did not differ significantly between the groups. Conclusion Patients who underwent single‐stage displaced BHMR and ACLR had significantly lower BHMR failure rate compared to those who underwent two‐stage surgery. Therefore, single‐stage displaced BHMR and ACLR should be advocated, although patient‐specific factors and further prospective studies remain important considerations. Level of Evidence Level III.